Identification of Coral Bleaching Attack Level using Coral Health Chart Method in Menjangan Kecil, Karimunjawa - Hanafi, Hanafi; Fitriani, Nabila Ayu; Athar, Muhammad Raihan; Hindami, Rio; Aulia, Indira Hauriina; Rachmawati, Siti Fitria; Irreniza, Kayla Yasmin; Anggiaputra, Nathanael Steffano Budi; Syahrodji, Putri Saqina Emilia; Fadlan, Azhardhya Norr Muhammad; Jeriansyah, Jejen; Riyanti, Riyanti; Arbanto, Bonifasius (Jurnal Biologi Tropis, 2024)
The increasing anthropogenic activities in Menjangan Kecil Waters can reduce the health condition of coral reefs in these waters. Therefore, it is necessary to investigate the level of bleaching attack that occurs in these waters. The purpose of this study was to determine the health condition of coral reefs in Menjangan Kecil Waters by observing the level of bleaching attack based on coral colour which is related to the density of zooxanthellae in coral living tissue. The CoralWatch method was applied to estimate the level of bleaching attack based on the level of coral colour in the coral health chart table. The results of this study revealed that the condition of coral reefs at 4 stations was dominated by colour levels 3-4, meaning that the condition of coral reefs began to bleach. The increasing of anthropogenic activities causes excessive interaction with coral reefs and human, thus accelerating the potential for bleaching. Optimization of ecotourism in Menjangan Kecil Waters, Karimunjawa needs to be done by conducting further studies on coral reef health.